P J Hoedemaker, teoloog en kerkman - D. J.C . van Wyk (HTS Teologiese Studies/Theological Studies, 1991)
P J Hoedemaker, theologian and man of God This article highlights aspects of P J Hoedemaker’s theology: It also deals with his academic work at the Vrije Universiteit, his views on the Scriptures and on historical criticism as well as his philosophical approach, concepts and formulation. Attention is also paid to his views on education, religious instruction and the university. His views on the state and his conflict with Doctor Kuyper on the subject are also dealt with.